Environmental Performance Assessment of Froth Flotation for Coal Recovery and Sulfur Removal from Ultrafine Coal Waste - Fundikwa, Bridget (Centre for Bioprocess Engineering Research, 2016)
The South African coal mining industry generates large volumes of coal ultrafine waste (< 150 microns) each year, with a significant amount being dumped in tailing slurry dams. These slurry dams have been associated with prolonged pollution and loss of valuable resources. In the two stage flotation process developed at the University of Cape Town, froth flotation is used to both recover coal (stage 1) and remove pyritic sulfur (stage 2) from ultrafine coal waste, resulting in three outputs streams: a saleable coal product, a small volume sulfide-rich stream, and a reduced volume sulfide lean tailings stream. Pre-disposal removal of sulfide sulfur and coal recovery by means of froth flotation is aimed at effectively removing the acid rock drainage (ARD) risk associated with sulfide bearing waste s and at recovering valuable resources respectively. Previous studies have demonstrated the technical feasibility of this process for a number of coal waste types on a laboratory-scale, with results indicating that it is possible to recover large quantities of useable coal whilst generating a tailings waste stream with a reduced sulfur content and negligible ARD risk. An order of magnitude financial model for a fictitious plant has also been developed, and applied to demonstrate the economic viability for s elected case studies. To date, however, studies on the environmental viability of the process have only focused on the ARD mitigating potential of the two-stage flotation process and little attention has been given to the systemic environmental implication s of the process such as the energy and reagent usage. The research study therefore aims to evaluate the environmental burdens and benefits of the two-stage flotation process, particularly from a South African context, and to compare the environmental performance to the conventional disposal of untreated coal ultrafines. Furthermore, this project aims to establish which stages along the process contribute the most to the environmental burdens of the process and how the variations of the input parameters affect the overall environmental performance of the proposed process. To this end, a life cycle inventory of inputs and outputs was compiled on the basis of the empirical results derived from a previous laboratory-scale case study conducted on a sample of an acid generating ultrafine coal waste from the Waterberg region. Experimental results from the case study, which entailed two-stage flotation (using Naflote 9858 as a coal collector and xanthate (SIBX) as a sulfide collector in stages 1 and 2), and detailed characterisation of the feed and desulfurised tailings, was supplemented with literature information and data from mass and energy balance calculations for a fictitious plant. An environmental impact analysis was subsequently conducted using a combination of Life Cycle Impact Assessment and risk-based impact assessment techniques and criteria. The impact categories selected included climate change, terrestrial acidification, fossil fuel depletion, natural land transformation, aquatic water pollution risk, drinking water quality risk, aqueous acidification, salinity and consumptive water footprint. Aquatic water pollution risk, drinking water quality risk and aqueous acidification impact indicators were calculated by summing up risk potential factors for the constituents of the final disposed waste streams. The rest of the impact categories were calculated by multiplying the inventory result with a characterisation factor developed from impact assessment models The case study results indicated that the simple mentation of the two-stage flotation process results in a notable decrease in eco-toxicity, salinity, consumptive water footprint, metal toxicity, aqueous acidification, fossil fuel depletion and natural land transformation impacts. However, the results al so indicated an increase in atmospheric related impacts (climate change and terrestrial acidification impacts), which has been attributed to the additional energy consumption associated with the two-stage flotation process and the production processes associated with the flotation reagents. Analyses of the process contributions to the individual impact categories for the two-stage flotation process revealed the climate change and terrestrial acidification impact categories to be dominated by the electricity production process and the flotation reagents production process. The sensitivity analyses revealed a higher dependence of the fossil fuel depletion impact category on the percentage coal yield than the electricity consumption of the foreground process. Furthermore the sensitivity analyses indicated a strong dependence of the climate change and terrestrial acidification impacts on the electricity consumption and the SIBX dosage in the foreground process. In the South African context, implementation the two-stage flotation process would result in a significant recovery of coal (approximately 1.2 million tonnes for every 4 million tonnes dry coal ultrafines lost per annum) and a sulfide-rich product which can be utilised for electricity production and sulfuric acid production respectively, hence promoting resource efficiency. Although higher than in the case of conventional land disposal, the energy used in the two-stage flotation process is infinitesimal compared to the energy recovered in the process through the generation of additional coal, and results in only a 0.025 % increase in the annual greenhouse gas emissions. The implementation of the two-stage flotation would also result in reduced water losses in comparison to conventional land disposal, which is beneficial in the South African context as South Africa is a water scarce region. Lastly whilst the implementation of the two-stage flotation process would result in the reduction of water related impacts associated with acidification, salinization and metal pollution, it might pose a further threat to aquatic life if the xanthate salt reagents are emitted to local water sources. The limitations of the study were mainly associated with the quality of the input and output data, the impact categories and the system boundary and scenario development. The multiple sources of information and the variations in literature of the energy input estimates were noted as a source of uncertainty. The lack of characterisation factors for some of the substances in the system as well as the exclusion of the possibility of utilization of the sulfide-lean stream were also part of the limitations associated with the study. Recommendations for future work include improving the environmental assessment by incorporating various case studies and by incorporating downstream processing as well as optimizing the two-stage flotation process by using less energy and by using less toxic flotation reagents.